1972
DOI: 10.1086/151254
|View full text |Cite|
|
Sign up to set email alerts
|

Gamma-Ray Observations of the Galactic Center and Some Possible Point Sources

Abstract: A (.5 m by .5 m) digitized spark chamber gamma ray telescope was flown on three balloon flights to look at the galactic center region, Virgo, and the Crab. An excess flux above atmospheric background of over four standard deviations was found for gamma rays exceeding 100 MeV coming from the galactic center region, corresponding to a line intensity of (2.0 +0.6) x 10 -4 y's(cm2 rad see),but there was no statistically significant excess in the 50 to 100 MeV interval, with a 95% confidence limit for the ratio EJ(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1972
1972
1995
1995

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Nonetheless, data from these at high energies (? 100 MeV), some positive results and other upper limits (Frye et al, 1971;Bennett et al, 1972;Fichtel et al, 1972;Dahlbacka et al, 1973;Sood et al, 1974;Frye et al, 1974), agree with the results shown in figure 9 within rather large uncertainties, except Frye et al (1974), who report values well below those shown.…”
Section: Resultssupporting
confidence: 73%
“…Nonetheless, data from these at high energies (? 100 MeV), some positive results and other upper limits (Frye et al, 1971;Bennett et al, 1972;Fichtel et al, 1972;Dahlbacka et al, 1973;Sood et al, 1974;Frye et al, 1974), agree with the results shown in figure 9 within rather large uncertainties, except Frye et al (1974), who report values well below those shown.…”
Section: Resultssupporting
confidence: 73%
“…given by Fichtel et al (1973), a more complete description of the detector system by Derdeyn et al (1972), and a discussion of calibration and data analysis procedures by Fichtel et al (1972) and Thompson (1973). During the period February 15 to 20, 1973, the region of the sky including the galactic plane from II = 2500 to II = 2900 was examined.…”
Section: Resultsmentioning
confidence: 99%
“…A more complete discussion of the SAS-II gamma ray telescope is given by Derdeyn et al (1972). The calibration and data analysis are similar to that used for previous balloon gamma ray digitized spark chambers (Fichtel et al, 1969;Kniffen, 1969;Fichtel et al, 1972;and Thompson, 1973).…”
Section: Description Of the Experimentsmentioning
confidence: 99%